Identifikasi Postur Kerja Pada Karyawan CV. Zam-Zam Furniture pada Penerapan Metode RULA - Septianto, Farras; Fasa, Nadia (Fakultas Teknik Universitas Tulang Bawang, 2024)
Zam-Zam Furniture makes bookshelves, shelves, tables, chairs, beds and wardrobes. Working conditions that threaten the safety and health of employees are considered dangerous. Fatigue or problems with the musculoskeletal system or muscles, such as body aches during work or after work, and muscle aches, are signs of danger to worker safety and health. As work is performed in inappropriate postures repeatedly, employees complain about inappropriate work postures. Most of the work is done manually, violating ergonomic rules. This research aims to determine employee work posture using the Rapid Upper Limb Assessment (RULA) method. The results show that one of the employees from CV Zam-Zam Furniture who was evaluated using the RULA method got a final score of 7; this shows that their attitude towards their work is in a dangerous state and that they must improve their position immediately. Keywords: Ergonomics, Final Score, Risk, RULA, Work Posture